2005
DOI: 10.1007/s10207-004-0059-3
|View full text |Cite
|
Sign up to set email alerts
|

Passive-attack analysis for connection-based anonymity systems

Abstract: In this paper we consider low-latency connection-based anonymity systems which can be used for applications like web browsing or SSH. Although several such systems have been designed and built, their anonymity has so far not been adequately evaluated.We analyse the anonymity of connection-based systems against global passive adversaries. We give a precise description of a packet-counting attack which requires a very low degree of precision from the adversary, evaluate its effectiveness against connection-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 20 publications
0
47
0
Order By: Relevance
“…While they are still considered "low-latency" connection-oriented approaches compared to slower message-based anonymity systems [20], they still exhibit non-trivial overhead and noticeable delay (as observed in Figure 1. In particular, a recent usability study [6] of Tor found that DNS requests were 40 times slower than direct connections.…”
Section: Related Workmentioning
confidence: 97%
“…While they are still considered "low-latency" connection-oriented approaches compared to slower message-based anonymity systems [20], they still exhibit non-trivial overhead and noticeable delay (as observed in Figure 1. In particular, a recent usability study [6] of Tor found that DNS requests were 40 times slower than direct connections.…”
Section: Related Workmentioning
confidence: 97%
“…Serjantov et al [8], for example, proposes the use of "spikes" in the traffic to find the communication relationship between users. Fu al.…”
Section: Modern Traffic Analysismentioning
confidence: 99%
“…Many attacks against MIXes and networks of MIXes exist. For example, Serjantov and Sewell [8] analyzed the possibility of a lone flow on an input link of a MIX. If the rate of this lone input flow is approximately equal to the rate of a flow out of the MIX, this pair of input and outflow flows are correlated.…”
Section: Modern Traffic Analysismentioning
confidence: 99%
“…B. N. Levine et al [52] presented a technique to thwart timing attacks in Mix-based systems. A. Serjantov and P. Sewell [53] investigated the time analysis for connection-based systems, e.g., Mix-based systems. X. Fu et al [54,55] proposed several attacking models based on traffic analysis, which are effective to thwart the anonymity in both wired and wireless systems.…”
Section: Attacking Attempts In Anonymous Systemsmentioning
confidence: 99%